Implemetasi Model Pembelajaran Teams Games Tournamen (TGT) Untuk Meningkatkan Minat Belajar Siswa Dan Pilar Anti Kekerasan - Hasyim, A. Wahid; Mufidah, Nuril; Muyassaroh, Hikmatul Faizah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2025)
This study aims to increase the mathematics learning interest of Grade X-G students at MAN Kota Pasuruan in the topic of statistics through the implementation of the Teams Games Tournament (TGT) learning model. This research is a Classroom Action Research (CAR) conducted in four cycles, covering the subtopics of Data Presentation, Measures of Central Tendency, Measures of Position, and Measures of Dispersion. The instruments used included a learning interest questionnaire, observation sheets, and documentation. The indicators of learning interest refer to Slameto's theory (2010), which includes feelings of enjoyment, interest, acceptance, and involvement. The results showed an increase in students’ learning interest from 55% in the pre-cycle to 87% in the fourth cycle. Thus, the TGT model has proven effective in enhancing students' interest in learning and can indirectly foster positive character values aligned with anti-violence principles, such as emotional regulation, tolerance, empathy, sportsmanship, and peaceful conflict resolution. Therefore, TGT can serve as an innovative alternative learning strategy for teaching statistics within the Merdeka Curriculum.